Optimizing the quality of horticultural crop: insights into pre-harvest practices in controlled environment agriculture - Zhao, Xinyi; Peng, Jie; Zhang, Li; Yang, Xiao; Qiu, Yujie; Cai, Chengcheng; Hu, Jiangtao; Huang, Tao; Liang, Ying; Li, Zonggeng; Tian, Mengliang; Liu, Fan; et al. (Frontiers in Plant Science, 2024)
In modern agriculture, Controlled Environment environment Agriculture agriculture (CEA) stands out as a contemporary production mode that leverages precise control over environmental conditions such as nutrients, temperature, light, and other factors to achieve efficient and high-quality agricultural production. Numerous studies have demonstrated the efficacy of manipulating these environmental factors in the short period before harvest to enhance crop yield and qualities quality in CEA. This comprehensive review aims to provide insight into various pre-harvest practices employed in CEA, including nutrient deprivation, nutrient supply, manipulation of the light environment, and the application of exogenous hormones, with the objective of improving yield and qualities quality in horticultural crops. Additionally, we propose an intelligent pre-harvest management system to cultivateproduce high-quality horticultural crops. This system integrates sensor technology, data analysis, and intelligent control, enabling the customization of specific pre-harvest strategies based on producers' requirements. The envisioned pre-harvest intelligent system holds the potential to enhance crop quality, increase yield, reduce resource wastage, and offer innovative ideas and technical support for the sustainable development of Controlled Environment AgricultureCEA.